The Silent Exodus: A Systematic Review of Quiet Quitting and Its Impact on Employee Productivity and Organizational Culture - Han Purnomo; Nur Wening; Rian Oktafiani (Jurnal Manajemen, 2025)
Quiet quitting refers to employees performing only their assigned duties without additional engagement, often triggered by a lack of appreciation, unfair compensation, job burnout, and an unsupportive organizational culture, which in turn affects productivity, employee retention, and organizational stability. This study aims to identify its causes, impact on employee productivity and organizational culture, and effective mitigation strategies. Using a Systematic Literature Review (SLR) with PRISMA guidelines, 12 relevant articles were selected from 78 identified in the Scopus database (2015–2025). Findings indicate that fair compensation, employee well-being, a positive work culture, and supportive leadership can reduce quiet quitting, while policies promoting work-life balance and transparent communication enhance employee engagement. These insights contribute to HR management strategies, with future research recommended to explore organizational interventions across industries for a more comprehensive approach.